2018
DOI: 10.1111/bcpt.12975
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Transforming Growth Factor‐β/Smad‐mediated Epithelial–Mesenchymal Transition by Celastrol Provides Protection against Bleomycin‐induced Pulmonary Fibrosis

Abstract: The respiratory disease pulmonary fibrosis (PF), which is characterized by scar formation throughout the lung, imposes a serious health burden. No effective drug without side effects has been proven to prevent this fatal lung disease. In this context, this study was undertaken to elucidate the protective effect of celastrol, a quinine methide pentacyclic triterpenoid from a Chinese medicinal plant 'thunder god vine' against bleomycin (BLM)-induced PF. We also attempted to study how the cytokine transforming gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 67 publications
2
19
0
Order By: Relevance
“…A large amount of evidence from experimental and clinical researches have highlight the important role of EMT in CCA metastasis . Celastrol has been reported to exhibit inhibitory effects on the progression of EMT in various of cancers . Our present studies proved that celastrol substantially inhibited the levels of epithelial marker E‐cadherin and decreased the levels of mesenchymal markers N‐cadherin and vimentin.…”
Section: Discussionsupporting
confidence: 70%
“…A large amount of evidence from experimental and clinical researches have highlight the important role of EMT in CCA metastasis . Celastrol has been reported to exhibit inhibitory effects on the progression of EMT in various of cancers . Our present studies proved that celastrol substantially inhibited the levels of epithelial marker E‐cadherin and decreased the levels of mesenchymal markers N‐cadherin and vimentin.…”
Section: Discussionsupporting
confidence: 70%
“…Studies have shown that TGF-β1 induced a significant increase in snail expression in human renal epithelial cells, accompanied by α-SMA up-regulation. These results demonstrated that snail is involved in the EMT process of human renal tubular epithelial cells [30]. The promotion of EMT in renal tubular epithelial cells by snail is regulated by many upstream signaling pathways, and Notch signaling pathway is one of them [9].…”
Section: Discussionmentioning
confidence: 72%
“…Local injection of steroid hormones into HTS mainly includes hydrocortisone acetate, dexamethasone, triamcinolone acetate, which could inhibit the expression of PDEF gene from reducing the collagen I and III synthesis and increase expression of cMyc and P53 gene to induce cell apoptosis, but the clinic effects were uncertain (Chen, Li, Kong, & Wang, ) Therefore, steroid therapy for HTS should be carefully selected. Bleomycin was a kind of cytotoxic antibiotic and commonly used in tumor treatment, which could be effective treatment of HTS with low recurrence rate and lower occurrence complications (Divya, Velavan, & Sudhandiran, ). Another antitumor medicine was 5‐FU, which could inhibit the proliferation of fibroblasts and even reduce blood vessels, decrease collagen synthesis, but cause pain while treatment (Ibrahim & Chalhoub, ).…”
Section: Strategies and Approaches To Prevention Of Myofibroblast Formentioning
confidence: 99%